2003
DOI: 10.2527/2003.811116x
|View full text |Cite
|
Sign up to set email alerts
|

Fenceline contact of beef calves with their dams at weaning reduces the negative effects of separation on behavior and growth rate1

Abstract: The purpose of this study was to examine the hypothesis that fenceline contact between beef calves and cows at weaning reduces indices of behavioral distress and associated temporary reductions in weight gain. One hundred Angus/Hereford-cross calves were randomly assigned to five treatments for 7 d in each of 3 yr to determine the effect of different weaning techniques on their behavior and subsequent growth. Treatments were 1) fenceline separation from dams on pasture (F-P), 2) total separation from dams on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 12 publications
6
112
2
Order By: Relevance
“…This was supported by the lying and standing/walking behaviour that changed during the observation period and was affected by weaning. In contrast to our study, Price et al (2003) also found a decrease in the time spent feeding as an indicator for weaning distress. On day 2, a lower feeding activity was observed compared with days 3 and 4 after weaning conducted with different methods.…”
Section: Behaviourcontrasting
confidence: 99%
See 1 more Smart Citation
“…This was supported by the lying and standing/walking behaviour that changed during the observation period and was affected by weaning. In contrast to our study, Price et al (2003) also found a decrease in the time spent feeding as an indicator for weaning distress. On day 2, a lower feeding activity was observed compared with days 3 and 4 after weaning conducted with different methods.…”
Section: Behaviourcontrasting
confidence: 99%
“…Studies in lambs emphasized the suitability of this method to reduce weaning stress (Schichowski et al, 2008). As another alternative, fence-line weaning allows the calf to have a certain level of social contact to the dam for several days while being prevented from suckling (Stookey et al, 1997;Price et al, 2003). However, these methods have drawbacks, and are for several reasons not widely used under practical conditions to reduce weaning stress in beef calves.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, calves in pastures adjacent to their dams were able to stand within a few metres of their dam following weaning, and unfortunately the authors do not report the behaviour of the calves if or when the dams were later moved to a distant enclosure. However, in a similar study, Price et al (2003) note that fence-line contact between calves and dams decreases over the 5 days following weaning, possibly as the calves and dams gradually become more independent of each other.…”
Section: The Role Of Maternal Deprivation Per Sementioning
confidence: 99%
“…Similarly, Lynch et al (2011) reported that deferring housing at the time of weaning resulted in a less marked stress response in beef calves (25%) compared with the traditional practice of weaning and simultaneous housing indoors at the end of the grazing season (62%; (Lynch et al, 2010) and 46% (Lynch et al, 2012) increases, respectively). Compared with abrupt weaning, practices such as progressive weaning or fenceline weaning have reduced the frequency of behavioural distress, heart rate and neutrophil:lymphocyte (N:L) ratio in calves (Church and Hudson, 1999;Price et al, 2003;Rasby, 2007). More recently, O'Loughlin et al (2011) reported that beef calves, particularly bulls, had a strong stress response and may benefit from a weaning strategy where they are allowed visual, oral and olfactory contact with the dam but are prevented from suckling for a number of days prior to total separation.…”
Section: Variablementioning
confidence: 99%